2021
DOI: 10.1016/j.redox.2021.102072
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evaluation of nucleophilic and electrophilic chemical probes for sulfenic acid: Reactivity, selectivity and biocompatibility

Abstract: Cysteine sulfenic acids (Cys-SOH) are pivotal modifications in thiol-based redox signaling and central intermediates en route to disulfide and sulfinic acid states. A core mission in our lab is to develop bioorthogonal chemical tools with the potential to answer mechanistic questions involving cysteine oxidation. Our group, among others, has contributed to the development of nucleophilic chemical probes for detecting sulfenic acids in living cells. Recently, another class of Cys-SOH prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Kinetic and fluorescence characterization of phenaline-1,3-dione derivatives. We first sought to assess the reactivity of phenaline-1,3-dione (1) and its analogs with an established small-molecule model for cysteine sulfenic acid, known as CSA 19,20 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic and fluorescence characterization of phenaline-1,3-dione derivatives. We first sought to assess the reactivity of phenaline-1,3-dione (1) and its analogs with an established small-molecule model for cysteine sulfenic acid, known as CSA 19,20 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…3). This Gpx3 variant has one redox-sensitive cysteine, C36 that is readily oxidized to sulfenic acid using stoichiometric amounts of hydrogen peroxide (H2O2) and has been well-validated as a model for the study of protein sulfenic acid reactivity 19,20 . Intact mass spectrometry (MS) analysis demonstrated that Gpx3 C36 sulfenic acid (Gpx3-SOH) formed the anticipated adduct with CysOx probes in high yield, while reduced Gpx3 (Gpx3-SH) was not modified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While this model, characterized in a handful of cases, can provide convenient answers to nagging questions surrounding target selectivity for a diffusible second messenger like H2O2 an equally troubling new set of selectivity issues arise, which cannot be satisfactorily addressed in target identification experiments that employ so-called "trap mutants" in which the peroxidase lacks the resolving cysteine. Furthermore, positing the redox relay as the exclusive mechanism of cysteine OxiPTM contradicts the proteome-wide discovery 28 of cysteine sulfenic and sulfinic acids OxiPTMs, known respectively as S-sulfenylation and S-sulfinylation, using reaction-based probes whose chemoselectivity has been shown in numerous reports 15,29 .…”
Section: Enzymatic and Non-enzymatic Mechanisms Of Post-translational...mentioning
confidence: 99%
“…Sulfenylation is a reversible oxidative modification where cysteine thiol is converted to a sulfenic acid (RS-OH) by reaction with two electron oxidants such as the peroxides H 2 O 2 or ONOO – ( Table 3 ; Alvarez and Radi, 2003 ; Yang et al, 2016 ); cysteine sulfenylation is reducible by common intracellular reductants such as reduced glutathione ( Reddie and Carroll, 2008 ; Conte and Carroll, 2013 ; Gupta and Carroll, 2014 ). In recent years, protein sulfenylation has been described in numerous systems due to the advent of dimedone-based and other sulfenylation-selective probes ( Holmila et al, 2018 ; Shi and Carroll, 2020 , 2021 ). In in vitro studies of recombinantly purified Sirt1, Sirt2, Sirt3, and Sirt5, sulfenylation was not detected by the DYn-2 dimedone-based probe following treatment with 100 μM H 2 O 2 ( Kalous et al, 2016 , 2020 ).…”
Section: Protein Oxidative Post-translational Modificationsmentioning
confidence: 99%